Estudio definitivo para el mejoramiento del camino vecinal Tioyacu – La Victoria, L=4.52 km. Distrito Elías Soplin Vargas, provincia de Rioja, región San Martín - Bardalez Bartra, Jorge Luis (2013)
This work has been developed in the Academic Professional School of Civil Engineering, Faculty of Civil Engineering and Architecture at the National University of San Martin Tarapoto purposes degree in Civil Engineering and implement the lessons learned in the Classroom university. This work was done for the purpose of participating in the solution of the existing road problems in rural areas of the province of Rioja, since the current situation of roads has problems walkability, generating costs of transporting the products countryside to the city are high and that the economy of farmers affected and therefore the quality of life for them; indeed, a road in poor condition as it has been studied, causes delays and discomfort in moving from the countryside to the city and vice versa, finding that although it is certain farm products are taken to the city, it is also true the farmer has to return to the field carrying products for subsistence, as well as those required for agriculture and other activities carried out in the field. So it has participated in the formulation of the project in question to achieve a local road affirmed. To develop this work has had to apply all the basics required in the area of ​​Transport, to work a road. This involves giving a technical solution to the problem, carrying out all activities necessary of which include: preliminary visits, surveying, topographic calculation, geometric design, road, earthwork and their volumes, transverse and longitudinal drains, design pavement, budget formulation, programming work and preparation of plans. As achievements we can state that the information has been obtained for the technical file of the project, the same that allow us to have the key document to look for financing the work. Moreover, as connoisseurs of bad state in which is currently the Way Neighborhood Tioyacu - y_ aware of our responsibility as an integral part of the National University of San Martin La Victoria, we are helping to solve this problem, posing improving said communication path, thereby benefiting will be the user communities of this route, noting that this project is of vital importance for being a purely agricultural and tourist area. In this way it contributes to economic and social development of neighboring villages, because the standard of living of its population increases, contributing to the development of our country, besides getting our knowledge are made. implement and develop our professional sense of the race.